2017
DOI: 10.1016/j.exger.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in dynamic fatigability and variability of arm and leg muscles: Associations with physical function

Abstract: Introduction It is not known whether the age-related increase in fatigability of fast dynamic contractions in lower limb muscles also occurs in upper limb muscles. We compared age-related fatigability and variability of maximal-effort repeated dynamic contractions in the knee extensor and elbow flexor muscles; and determined associations between fatigability, variability of velocity between contractions and functional performance. Methods 35 young (16 males; 21.0±2.6 years) and 32 old (18 males; 71.3±6.2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 71 publications
(112 reference statements)
5
55
0
Order By: Relevance
“…Although females were weaker, slower and exhibited lower rates of neuromuscular activation for the plantar flexors than males (Table 1), females were less fatigable, which is a different outcome than the limited number of reports on sex-related fatigue differences for maximal effort unconstrained shortening velocity tasks in other muscle groups (Senefeld et al 2013(Senefeld et al , 2016. The differences may be owing to muscle fibre composition or activity patterns.…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…Although females were weaker, slower and exhibited lower rates of neuromuscular activation for the plantar flexors than males (Table 1), females were less fatigable, which is a different outcome than the limited number of reports on sex-related fatigue differences for maximal effort unconstrained shortening velocity tasks in other muscle groups (Senefeld et al 2013(Senefeld et al , 2016. The differences may be owing to muscle fibre composition or activity patterns.…”
Section: Discussionmentioning
confidence: 40%
“…Studies focusing on the elbow flexors and knee extensors suggest that both sexes demonstrate similar decrements in peak power (Senefeld et al 2013(Senefeld et al , 2016. Yoon et al (2015) reported that females were less fatigable than males during slow-velocity (~60º/s), low-resistance (20% MVC) elbow flexions until task failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our findings confirm that maximal force capacity is more preserved with advanced age in healthy adults during maximal eccentric contractions than during isometric and concentric contractions at a relatively slow-to-moderate velocity of 60°/s in the upper limb. This velocity corresponds to ~15–20% of maximal elbow flexion velocity for the young adults (~380°/s with a 20% MVIC load) and old adults (~320°/s with a 20% MVIC load) (Yoon et al 2013; Senefeld et al 2017). Furthermore, and as discussed below, because voluntary activation did not differ between contraction types, the relative preservation of the torque during eccentric contractions compared with the other contraction types with aging is likely due to muscular mechanisms.…”
Section: Discussionmentioning
confidence: 99%